The retrieval of ethics - Brewer, Talbot (Oxford : Oxford University Press, 2009)
Talbot Brewer offers a new approach to ethical theory, founded on a far-reaching reconsideration of the nature and sources of human agency. He argues that ethical reflection is itself an important life activity, and philosophical ethics is an extension of this practical activity rather than just a theoretical reflection upon it.
Many ideas presented at graduate seminars, audiences at various universities and colleges, and various conferences.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ethics